Beyond The Supermarket: Lost Opportunities In Summer Study Abroad For Singapore Sojourners In Australia - Bell, Maureen (Penerbit Universiti Sains Malaysia (USM Press), 2008)
The experiences of a group of Singaporean students on a summer study abroad programme in Australia are explored in this case study. The case is discussed within the context of the complex mix of influences operating on higher education innovations for internationalisation in Singapore, including the development of Singaporean students as global citizens and Australian offerings for the Asia Pacific higher education market. The vision and purpose of the summer study abroad programme, the students' motivations and development of cultural perspectives, the students' views of the teaching and learning strategies, and teaching styles are explored. The case study draws attention to a variety of issues regarding summer study abroad in Australia for Singaporean and possibly other Asia Pacific students; in particular the importance of, and the logistical barriers to, inter-cultural student engagement. Implications include the need to challenge stereotypical views of Singaporean and Australian students, provide structured opportunities for inter-cultural engagement, appropriate teaching and learning strategies, and support for a reflective approach to inter-cultural learning combined with strategies for developing the student group as a community of learners.